2000
DOI: 10.1152/ajprenal.2000.278.1.f29
|View full text |Cite
|
Sign up to set email alerts
|

Localization and regulation of PKA-phosphorylated AQP2 in response to V2-receptor agonist/antagonist treatment

Abstract: Phosphorylation of Ser(256), in a PKA consensus site, in AQP2 (p-AQP2) appears to be critically involved in the vasopressin-induced trafficking of AQP2. In the present study, affinity-purified antibodies that selectively recognize AQP2 phosphorylated at Ser(256) were developed. These antibodies were used to determine 1) the subcellular localization of p-AQP2 in rat kidney and 2) changes in distribution and/or levels of p-AQP2 in response to [desamino-Cys(1),D-Arg(8)]vasopressin (DDAVP) treatment or V(2)-recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
148
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(159 citation statements)
references
References 54 publications
9
148
1
1
Order By: Relevance
“…Phosphorylation of AQP2 at Ser 256 is essential but not sufficient for steady-state expression of AQP2 at the cell surface (10,12,25,38). We investigated the Ser 256 phosphorylation state of AQP2 that accumulates at the cell surface and in the trans-Golgi region following hypertonic challenge by comparing hypertonicity-induced accumulation of AQP2 in both regions of LLC-PK 1 cells stably expressing mutants that either mimic Ser 256 -phosphorylated (LLC-AQP2 (S256D)) or nonphosphorylated (LLC-AQP2 (S256A)) AQP2 (Fig.…”
Section: Acute Hypertonicity Induces Segregation Of Ser 256 -Phosphormentioning
confidence: 99%
“…Phosphorylation of AQP2 at Ser 256 is essential but not sufficient for steady-state expression of AQP2 at the cell surface (10,12,25,38). We investigated the Ser 256 phosphorylation state of AQP2 that accumulates at the cell surface and in the trans-Golgi region following hypertonic challenge by comparing hypertonicity-induced accumulation of AQP2 in both regions of LLC-PK 1 cells stably expressing mutants that either mimic Ser 256 -phosphorylated (LLC-AQP2 (S256D)) or nonphosphorylated (LLC-AQP2 (S256A)) AQP2 (Fig.…”
Section: Acute Hypertonicity Induces Segregation Of Ser 256 -Phosphormentioning
confidence: 99%
“…Rabbit polyclonal antibodies against AQP2 (Sigma-Aldrich), Ser256 phosphorylated AQP2 (p-AQP2) (12), AQP1 (Chemicon, Temecula, CA), AQP3 (a gift from J.-M. Verbavatz, CEA Saclay), extracellular signal-regulated kinase 1/2 (ERK1/2; C16) and Tyr204 p-ERK1/2 (Santa Cruz Biotechnologies, Santa Cruz, CA), mouse monoclonal RhoA and Ser188 p-RhoA (Santa Cruz Biotechnologies), and mouse mAb against ␤-actin (Sigma-Aldrich) were used.…”
Section: Antibodiesmentioning
confidence: 99%
“…In normal CD cells, the stimulation of V2R by AVP leads to the phosphorylation of AQP2 on the Ser256 residue and its subsequent insertion in the apical plasma membrane, an essential step to mediate final urine concentration (12,13). A mild impairment in urinary concentrating ability, with increased circulating AVP levels, has been described in patients with ADPKD and cystic kidneys (11,14,15).…”
mentioning
confidence: 99%
“…Affinitypurified polyclonal antibodies against the renal sodium transporters/ channels (24) (NHE3, NKCC2, thiazide-sensitive Na-Cl co-transporter [NCC], the ENaC subunits), aquaporin 2 (AQP2) and phosphorylated-AQP2 (p-AQP2) (25) were used. A sheep polyclonal antibody to 11␤HSD2 (Chemicon, Temecula, CA) was commercially obtained.…”
Section: Primary Antibodiesmentioning
confidence: 99%
“…Moreover, semiquantitative immunoblotting with antibodies that selectively recognize AQP2 (p-AQP2), which is phosphorylated in the protein kinase A phosphorylation consensus site (Ser256) (25), demonstrated that the abundance of p-AQP2 was also increased in the inner medulla (198 Ϯ 28 versus 100 Ϯ 15%; P Ͻ 0.05) but was not changed in the cortex/OSOM (100 Ϯ 7 versus 100 Ϯ 9%; NS) and ISOM (98 Ϯ 7 versus 100 Ϯ 15%; NS).…”
Section: Increased Protein Abundance and Apical Plasma Membrane Targementioning
confidence: 99%